ANALISIS METODE PELAKSANAAN PEMBANGUNAN BANGUNAN BAMBU REGENERATIVE FARMING LEARNING CENTER (RFLC) SUBAK UMA LAMBING SIBANGKAJA - TJOKORDA ISTRI PRAGANINGRUM; I GEDE ANGGA DIPUTERA; WAYAN GDE ADI ANANTAWIJAYA (Universitas Mahasaraswati K. Mataram, 2022)
Overall development continues from time to time. Bali as a tourist destination also always strives to improve its quality by carrying out various developments, especially in fields that support tourism activities. Bali with its natural wealth uses bamboo as the basis for buildings. Apart from being a natural material, it also has a high aesthetic value. However, it must be realized that the use of bamboo material requires special skills and methods that are different from the use of other materials. One of the buildings that uses bamboo is the Regenerative Farming Learning Center (RLFC) Subak Uma Lambing Sibangkaja. This study aims to determine in detail how the construction method for buildings with bamboo material is and how it relates to costs and implementation time. The method used is descriptive with qualitative and quantitative approaches. The author makes observations to observe the stages of activities, material specifications and workmanship techniques during the construction process. Based on the results of the analysis obtained a description of the stages of each work starting from foundation work to finishing. It is known that the cost of constructing the RLFC building is Rp. 241,054.000,00 and the processing time required in the manufacture of this RFLC bamboo building is 7 weeks or 49 days